Simulation study of the digital temperature sensor operation in case of a non-standard mechanical impact of the NPP equipment - Bikovsky, Y.M.; Derevianko, O.V.; Levchenko, V.V.; Pogosov, A.Y. (Вопросы атомной науки и техники, 2020)
The article presents the results of an experimental study relevant to the effective organization of temperature control of thermomechanical equipment at nuclear power plants (turbines, pumps, steam generators, deaerators, etc.). Bench studies of the reaction of the DS18B20 digital intelligent temperature sensor, which is supposed to be introduced at Ukrainian nuclear power plants, to the application of external compression force to its body, which may occur under conditions typical for the operation of equipment operating at nuclear power plants, have been carried out. An electrical circuit diagram has been developed for a reset signal simulation device (for bench modeling of a sensor application system). The issues of identifying a sign in the sensor output signal informing about the effect of an external compression force on its body are considered. The technique of bench experiments and processing of research results necessary to address the issue of introducing new digital measuring equipment for temperature control of thermomechanical equipment of nuclear power plants is given. Представлено результати експериментального дослідження, актуального для ефективної організації контролю температури тепломеханічного обладнання на АЕС (турбін, насосів, парогенераторів, деаераторів та ін.). Проведено стендові дослідження реакції цифрового інтелектуального датчика температури DS18B20, передбачуваного до впровадження на АЕС України, на дію зовнішньої сили стиснення на його корпус, яка може виникнути в умовах, характерних для експлуатації діючого на АЕС обладнання. Розроблена електрична принципова схема пристрою імітації сигналу «скидання» (для стендового моделювання системи застосування датчика). Розглянуто питання виявлення у вихідному сигналі датчика ознаки, що інформує про вплив зовнішньої сили стиснення на його корпус. Наведено методику проведення стендових експериментів та обробки результатів досліджень, необхідних для вирішення питання про впровадження нових цифрових засобів вимірювальної техніки для контролю температури тепломеханічного обладнання АЕС. Представлены результаты экспериментального исследования, актуального для эффективной организации контроля температуры тепломеханического оборудования на АЭС (турбин, насосов, парогенераторов, деаэраторов и др.). Проведены стендовые исследования реакции цифрового интеллектуального датчика температуры DS18B20, предполагаемого к внедрению на АЭС Украины, на приложение внешней силы сжатия на его корпус, которая может возникнуть в условиях, характерных для эксплуатации действующего на АЭС оборудования. Разработана электрическая принципиальная схема устройства имитации сигнала «сброс» (для стендового моделирования системы применения датчика). Рассмотрены вопросы выявления в выходном сигнале датчика признака, информирующего о воздействии внешней силы сжатия на его корпус. Приведена методика проведения стендовых экспериментов и обработки результатов исследований, необходимых для решения вопроса о внедрении новых цифровых средств измерительной техники для контроля температуры тепломеханического оборудования АЭС.